Manual Validation and Calibration Method for All-or-Nothing Traffic Assignment - Hitapriya Suprayitno (IPTEK Journal of Proceedings Series, 2017)
Transport Modelling is capital for transportation planning. All-or-Nothing Traffic Assignment is used quite a lot. The model can not be considered valid without passing through validation and calibration process. A validation and calibration method, for the all-or-nothing traffic assignment, need to be developed. The research produced simple practical validation and calibration method. The calculated model traffic volumes are compared against the real traffic volumes. Simple validation method was developed by just setting a maximum allowable error, measured in precentage. Simple calibration method consists of correcting the model traffic volume by correcting the corresponding OD Matrix cell values. The calibration consists of 4 basic tasks : 1. identifying the traffic volume need to be calibrated, 2. identifying corresponding OD matrix cells corresponding to the traffic volume need to be calibrated, 3. distributing traffic volume error to the coresponding OD matrix cells, and 4. developing the calibrated OD matrix. Validation and Calibration are a pair of an iterative process.